A shariah evaluation on drug abuse: justifications in imposing severe punishment for drug addicts in Malaysia - Mohd Noor, Azman; Mohd. Zain, Nor Razinah; Saleh, Abdulmajid Obaid Hasan (2020)
Introduction: Societal-related problems relating to drug abuse is not a new issue in Malaysia. Drug abuse is considered as No.1 enemy of the country and continuous efforts have been made by a variety of stakeholders (especially Malaysian government) in combating it. The government has spent a huge financial allocation to build rehabilitation centres to provide treatments to drug addicts. Looking closely to the principles of Shariah, the Fiqhi discourse relating to drug abuse should not be ignored. Moreover, the prevailing numbers of drug addicts in Malaysia are unfortunately males and professing the religion of Islam. Material and methods: by employing a qualitative investigation methods and doctrinal legal analysis, this research looks into both aspects of current applicable laws and relevant Shariah discourse on drug abuse. This research focuses on the issue of drug addiction and whether it should be considered as a disease that justified an exemption from any punishment. Results: After the evaluation of principles that derived from Shariah with references to Al-Qur’an, Sunnah, and Ijtihad, it is found that the current laws in punishing drug abuse is relevant and correct. Furthermore, this study suggests that drug addicts should be blamed for such drug abuse and should be sentenced accordingly. Conclusion: Drug abuse is dangerous to an individual’s health either physically or mentally. Thus, severe punishments can be used a mitigation effort in preventing occurrences of drug abuses among drug addicts themselves and to stop such drug abuse in the society.